Student Soft Skill Development: Fiqh Teacher Problems at MTsS Al-Fuad Seruway Aceh Tamiang - Fakhri Rizky Putra; Muhammad Ichsan (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2025)
Abstract In the world of education varied learning methods are very necessary in order to support the needs of students' hard skills and soft skills. Soft skills themselves are interpreted as abilities beyond technical and academic abilities, which prioritize the formation of the character of students so that they are able to compete, ethical, moral, courtesy and interact with the community. The purpose of this study is to see whether the talent Soft Skill of Communication and Cooperation in Class 9 MTs students can be channeled through the learning process of fiqh carried out by teachers and students in the classroom. This study uses a qualitative method with the MTSS Al-Fuad Seruway Aceh Tamiang field research design. Data collection techniques are carried out by interview and observation methods that have been taken in the field to see the development of student soft skills talents. The results of this study were found that the main problematic in fiqh learning in class 9 MTs lies in the dominant use of the lecture method is unable to encourage students to be actively involved in the learning process, environmental factors and students who do not support, students tend to be passively reflected in the fact that almost half of students in the class sleep, the limitations of facilities and infrastructure, the learning approach used is very adequate to be able student. This condition indicates that various aspects of soft skills such as discipline, responsibility, collaboration, and confidence have not been realized optimally. Therefore, it is necessary to develop a more interactive and collaborative learning method so that the learning process does not only focus on cognitive achievement, but also on the formation of students' social character and skills. Abstrak Pada dunia pendidikan metode pembelajaran yang variatif sangat diperlukan demi menunjang kebutuhan hard skill maupun soft skill siswa. Soft skill itu sendiri diartikan sebagai kemampuan di luar kemampuan teknis dan akademis, yang lebih mengutamakan pembentukan karakter peserta didik sehingga mampu bersaing, beretika, bermoral, sopan santun dan berinteraksi dengan masyarakat. Tujuan penelitian ini untuk melihat bagaimana bakat soft skill komunikasi dan kerjasama yang ada pada siswa kelas 9 MTsS Al-fuad Seruway Aceh Tamiang dapat tersalurkan melalui proses pembelajaran fiqih yang dilaksanakan oleh guru dan siswa di kelas. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian lapangan. Teknik pengumpulan data dilakukan dengan metode wawancara dan observasi untuk melihat perkembangan bakat soft skill komunikasi dan kerjasama siswa. Hasil dari penelitian ini ditemukan bahwa dalam pembelajaran fiqih di kelas 9 penggunaan metode ceramah secara dominan tidak mampu mendorong siswa untuk terlibat aktif dalam proses pembelajaran, faktor lingkungan dan karakter siswa yang belum mendukung, siswa cenderung pasif tercermin dari kenyataan bahwa hampir setengah dari siswa dalam kelas tertidur, keterbatasan fasilitas dan infrastruktur, pendekatan pembelajaran yang digunakan sangat berpegang teguh terhadap norma dan hanya norma-norma teks dari teks tanpa ilustrasi yang berkaitan dengan konteks sosial dan budaya siswa. Kondisi ini menandakan bahwa aspek soft skill komunikasi dan kerjasama belum terealisasikan secara optimal. Oleh karena itu, diperlukan pengembangan metode pembelajaran yang lebih interaktif dan kolaboratif agar proses pembelajaran tidak hanya berfokus pada pencapaian kognitif, tetapi juga pada pembentukan karakter dan keterampilan sosial siswa.